An Analytical Study on Health and Safety of Differently-Abled Workforce Employed in Indian IT Organizations - K , Raghavi; N. , Gopinathan (International Journal of Psychosocial Rehabilitation, 2020)
Life is a roller coaster filled with a lot of thrills, twists, and turns. Once your ride is complete, you get down with a big sigh of relief but do not stop there; instead, try it once more. In this fast-paced life, survival becomes very difficult if you are not able to sell, and one such place to prove your skills is the workplace. In this research article we use the term differently abled instead of disabled as society is fast approaching a pace where there is no discrimination. Providing health and safety to differently-abled people is a major and visible factor of ethical business. The paper focuses on the health and safety of differently-abled employees in Indian IT organizations w.r.t. Chennai. A sample of 20 was collected from various differently-abled employees in IT organizations. The aim of the paper is to find out from the targeted respondents if they have provisions for proper health and safety at the workplace and give suggestions for the same.